UNDERSTANDING THE UNKNOWN: WORK DISCUSSION AS A MEANS OF DEVELOPING CASE-UNDERSTANDING COMPETENCIES - Kampe, Robert (International Journal of Child, Youth and Family Studies, 2025)
In the context of academic training for social educators in Vienna, increasing emphasis is being placed on supporting the development of core competencies with a focus on forming a detailed appreciation of the client’s situation — “case understanding”. The method of Work Discussion described in this article is based on a psychodynamic theory founded in the psychoanalytic tradition. It enables seminar groups to reflect on, and think in a differentiated manner about, interactions and relationship dynamics between people in psychosocial fields of work. The article introduces key ideas on the professionalism of social pedagogical professionals and explains common theories of professionalization in this research field. Using the example of Work Discussion, I elaborate characteristics of psychodynamically oriented professionalization in academic education and training for social work professionals. The final part of the article is a discussion of how psychodynamically oriented professionalism could facilitate a transformation in professional practice.